2012
DOI: 10.1007/s00253-012-4547-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-digestion of manure and whey for in situ biogas upgrading by the addition of H2: process performance and microbial insights

Abstract: In situ biogas upgrading was conducted by introducing H(2) directly to the anaerobic reactor. As H(2) addition is associated with consumption of the CO(2) in the biogas reactor, pH increased to higher than 8.0 when manure alone was used as substrate. By co-digestion of manure with acidic whey, the pH in the anaerobic reactor with the addition of hydrogen could be maintained below 8.0, which did not have inhibition to the anaerobic process. The H(2) distribution systems (diffusers with different pore sizes) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
132
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(149 citation statements)
references
References 40 publications
15
132
2
Order By: Relevance
“…The process enriches microbial consortia that are mainly composed of prokaryotic communities to convert mixtures of organic matter including agricultural, animal, or food waste into biogas with methane content of 50-70 % (Luo and Angelidaki 2013;Town et al 2014). Owing to the improvement of nutrient balance and buffer capacity, a variety of studies have demonstrated the enhancement effect of co-fermentation on the process performance (Ye et al 2013;Ferrer et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The process enriches microbial consortia that are mainly composed of prokaryotic communities to convert mixtures of organic matter including agricultural, animal, or food waste into biogas with methane content of 50-70 % (Luo and Angelidaki 2013;Town et al 2014). Owing to the improvement of nutrient balance and buffer capacity, a variety of studies have demonstrated the enhancement effect of co-fermentation on the process performance (Ye et al 2013;Ferrer et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The production of biogas via AD is a complex process, involving many different microbial species [2]. The complex organic compounds are first hydrolyzed into oligomers and monomers, and then further converted to acetate, CO 2 , and H 2 by various fermenting bacteria. The methanogenesis is the final step to convert acetate, CO 2 , and H 2 to CH 4 by methanogenic archaea.…”
Section: Introductionmentioning
confidence: 99%
“…The complex organic compounds are first hydrolyzed into oligomers and monomers, and then further converted to acetate, CO 2 , and H 2 by various fermenting bacteria. The methanogenesis is the final step to convert acetate, CO 2 , and H 2 to CH 4 by methanogenic archaea. The syntrophic relationship between bacteria and archaea is essential for the stability of the biogas process [3].…”
Section: Introductionmentioning
confidence: 99%
“…These methods are performed outside of the anaerobic reactor for biogas upgrading which requires extra investments. Previous studies have shown that CH4 in AD can be increased by adding inorganic electron donors such as H2 and CO (Luo & Angelidaki, 2013). These can, for example, be produced as syngas from wood through a gasification process.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen can be used to upgrade the methane production directly in the reactor by increasing the hydrogenotrophic methanogenesis (Luo & Angelidaki, 2013), which consumes hydrogen together with CO2 in the biogas, with methane as product (Luo & Angelidaki, 2012):…”
Section: Introductionmentioning
confidence: 99%